2020
DOI: 10.1002/mc.23248
|View full text |Cite
|
Sign up to set email alerts
|

MYC‐binding lncRNA EPIC1 promotes AKT‐mTORC1 signaling and rapamycin resistance in breast and ovarian cancer

Abstract: AKT‐mTORC1 (mammalian target of rapamycin complex 1) signaling pathway plays a critical role in tumorigenesis and can be targeted by rapamycin. However, the underlying mechanism of how long noncoding RNA (lncRNAs) regulate the AKT‐mTORC1 pathway remains unclear. EPIC1 (epigenetically‐induced lncRNA 1) is a Myc‐binding lncRNA, which has been previously demonstrated to be overexpressed in multiple cancer types. In a pathway analysis including 4962 cancer patients, we observed that lncRNA EPIC1 expression was pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Depletion of TMPO-AS1 suppressed the EMT and motility and 5-FU resistance in ovarian cancer cells ( Li et al, 2020b ). LncRNA EPIC1 enhanced rapamycin resistance via activation of AKT-mTORC1 pathway in ovarian cancer ( Wang et al, 2020b ). Myc was involved in EPIC1-mediated oncogenesis in ovarian cancer cells.…”
Section: Lncrnas Regulate 5-fu and Rapamycin Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…Depletion of TMPO-AS1 suppressed the EMT and motility and 5-FU resistance in ovarian cancer cells ( Li et al, 2020b ). LncRNA EPIC1 enhanced rapamycin resistance via activation of AKT-mTORC1 pathway in ovarian cancer ( Wang et al, 2020b ). Myc was involved in EPIC1-mediated oncogenesis in ovarian cancer cells.…”
Section: Lncrnas Regulate 5-fu and Rapamycin Resistancementioning
confidence: 99%
“…Myc was involved in EPIC1-mediated oncogenesis in ovarian cancer cells. Overexpression of lncRNA EPIC1 activated the AKT-mTORC1 pathway via Myc and caused rapamycin resistance in ovarian cancer ( Wang et al, 2020b ).…”
Section: Lncrnas Regulate 5-fu and Rapamycin Resistancementioning
confidence: 99%
“…One of its forms, mTORC1, transfers extracellular Gln into cells in the absence of amino acids (13). In ovarian cancer cells, mTORC1 is closely associated with Gln metabolism, and the mTORC1 signaling pathway is inhibited if the expression of the glutamine transporter is silenced (14). Pusapati et al found that combined inhibition of glycolysis and mTORC1 signaling disrupts metabolic reprogramming in ovarian cancer cells and inhibits their growth in vitro and in vivo (15).…”
Section: Mtorc1mentioning
confidence: 99%
“…One of its forms, mTORC1, transfers extracellular Gln into cells in the absence of amino acids ( 13 ). In ovarian cancer cells, mTORC1 is closely associated with Gln metabolism, and the mTORC1 signaling pathway is inhibited if the expression of the glutamine transporter is silenced ( 14 ). Pusapati et al.…”
Section: Related Signals and Genes Regulating Gln Metabolism In Ovari...mentioning
confidence: 99%
“…The mTOR-specific inhibitor rapamycin is used for the therapy of some types of cancer, but cases of resistance to this drug have been described [ 264 ]. EPIC1 knockdown makes resistant breast and ovarian cancer cells sensitive to rapamycin [ 252 ]. High expression of EPIC1 lncRNA accelerates proliferation of lung cancer cells [ 243 ] and cholangiocarcinoma cells [ 224 ] and enhances invasive growth of colon cancer cells [ 229 ].…”
Section: Lncrnamentioning
confidence: 99%